Cell Surface Proteome of Dental Pulp Stem Cells Identified by Label-Free Mass Spectrometry - Niehage, Christian; Karbanová, Jana; Steenblock, Charlotte; Corbeil, Denis; Hoflack, Bernard (PLOS ONE, 2016)
Multipotent mesenchymal stromal cells (MSCs) are promising tools for regenerative medicine. They can be isolated from different sources based on their plastic-adherence property. The identification of reliable cell surface markers thus becomes the Holy Grail for their prospective isolation. Here, we determine the cell surface proteomes of human dental pulp-derived MSCs isolated from single donors after culture expansion in low (2%) or high (10%) serum-containing media. Cell surface proteins were tagged on intact cells using cell impermeable, cleavable sulfo-NHS-SS-biotin, which allows their enrichment by streptavidin pull-down. For the proteomic analyses, we first compared label-free methods to analyze cell surface proteomes i.e. composition, enrichment and proteomic differences, and we developed a new mathematical model to determine cell surface protein enrichment using a combinatorial gene ontology query. Using this workflow, we identified 101 cluster of differentiation (CD) markers and 286 non-CD cell surface proteins. Based on this proteome profiling, we identified 14 cell surface proteins, which varied consistently in abundance when cells were cultured under low or high serum conditions. Collectively, our analytical methods provide a basis for identifying the cell surface proteome of dental pulp stem cells isolated from single donors and its evolution during culture or differentiation. Our data provide a comprehensive cell surface proteome for the precise identification of dental pulp-derived MSC populations and their isolation for potential therapeutic intervention.